What are the financial systemic implications of access and non-access to Federal Reserve deposit accounts for central counterparties? - Maggie Sklar (Federal Reserve Bank of Chicago, 2020)
In this working paper, I examine the interconnections between designated derivatives central counterparties (CCPs) with Federal Reserve deposit accounts and non-designated CCPs and the potential financial stability implications. This working paper notes the interconnections between the non-designated and designated derivatives CCPs through their clearing members and the commercial custodial banks they utilize to hold and transfer collateral. The paper then identifies additional potential contagion risks and financial stability risks, including liquidity risk, market risk, concentration risk, and loss of confidence more broadly. Although there are a number of research articles addressing these topics with respect to designated CCPs or OTC derivatives, this working paper includes the perspective looking at U.S. futures CCPs and nondesignated CCPs.
Keywords: 330; Clearing; Interbankenmarkt; Bankenliquidität; Refinanzierung